Preferential Disomic Segregation and C. micrantha/C. medica Interspecific Recombination in Tetraploid ‘Giant Key’ Lime; Outlook for Triploid Lime Breeding - Ahmed, Dalel; Curk, Franck; Evrard, Jean Charles; Froelicher, Yann; Ollitrault, Patrick (Frontiers in Plant Science, 2020)
The triploid ‘Tahiti’ lime (C. x latifolia (Yu. Tanaka) Tanaka) naturally originated from a merger between a haploid ovule of lemon (C. x limon (L.) Burm) and a diploid pollen from a ‘Mexican’ lime (C. x aurantiifolia (Christm.) Swing). The very limited natural inter-varietal diversity and gametic sterility of C. latifolia requires a phylogenomic based reconstruction breeding strategy to insure its diversification. We developed a strategy based on interploid hybridization between diploid lemon and the doubled diploid ‘Giant Key’ lime. This lime is a doubled diploid of ‘Mexican’ lime, itself a natural interspecific F1 hybrid between C. medica L. and C. micrantha Wester. For an optimized breeding program, we analyzed the meiotic behavior of the allotetraploid lime, the genetic structure of its diploid gametes, the interspecific recombination between C. medica and C. micrantha, and constructed its genetic map. A population of 272 triploid hybrids was generated using ‘Giant Key’ lime as pollinator. 158 SNPs diagnostic of C. micrantha, regularly distributed throughout the citrus genome were successfully developed and applied. The genetic structure of the diploid gametes was examined based on C. micrantha doses along the genome. The diploid gametes transmitted in average 91.17% of the parental interspecific C. medica / C. micrantha heterozygosity. Three chromosomes (2, 8 and 9) showed disomic segregation with high preferential pairing values, while the remaining chromosomes showed an intermediate inheritance with a preferential disomic trend. A total of 131 SNPs were assigned to nine linkage groups to construct the genetic map. It spanned 272.8 cM with a low average recombination rate (0.99 cM Mb-1) and high synteny and colinearity with the reference clementine genome. Our results confirmed that an efficient reconstruction breeding strategy for ‘Tahiti’ lime is possible, based on interploid hybridization using a doubled diploid of C. aurantiifolia. The tetraploid parent should be selected for favorable agronomic traits and its genetic value should be efficiently inherited by the progeny thanks to transmission of the high level of parental heterozygosity. However, it would require developing numerous progeny to overcome the linkage drag caused by the limited interspecific recombination associated with the predominant disomic inheritance.